Applied Fairness Theory: Comment - Holcombe, Randall G. (American Economic Review, 2016)
William Baumol (1982) presented a provocative and potentially valuable piece of analysis on fairness, but his contribution suffers from the flaw of defining terms in a manner similar to, but with important differences from, their common definitions. As a result of this terminological problem, it would be possible for a real world outcome to be fair (or even superfair) according to Baumol's criteria, but to be unfair according to the commonly accepted meaning of the word. Conversely, what would commonly be accepted as fair in the real world might not be fair according to Baumol's criteria. My objection here is largely with Baumol's terminology, but its significance extends well beyond terminology because it affects the way economists think about equity issues, ranging from the particular case of fairness theory to welfare economics in general.' The remarks that follow fall into two categories. First, I argue that it is unfair (in the traditional meaning of the word) for Baumol to redefine the meaning of Second, I argue that fair outcomes can only be judged within the context of the institutional setting that produces the outcomes. As a result, any analysis like Baumol's, which examines only the outcome of a process without examining the process itself, can never determine whether an outcome is fair.